2020
DOI: 10.12657/denbio.084.006
|View full text |Cite
|
Sign up to set email alerts
|

Species composition of arthropods on six understory plant species growing in high and low light conditions

Abstract: The quality of leaves as food for insects is affected both by plant species and the light conditions present during growth. Little information exists concerning the impact of these factors on the diversity of insects that live in the forest understory. We studied arthropod fauna on six understory plant species commonly occurring in Europe. Different groups of herbivorous insects were identified, as well as predatory insects and arachnids. We analysed the influence of both plant species and light conditions dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…Field observations (unpublished data) of leaves have indicated significant damage caused by the feeding of the monophagous moth Yponomeuta evonymellus L. (Lepidoptera) and polyphagous beetles, such as Gonioctena quinquepunctata F. and Phyllobius sp. (Coleoptera), which prefer Prunus padus L. and P. serotina leaves [50][51][52][53]. Wounds are the gateway to infection by pathogens of this type [54].…”
Section: Discussionmentioning
confidence: 99%
“…Field observations (unpublished data) of leaves have indicated significant damage caused by the feeding of the monophagous moth Yponomeuta evonymellus L. (Lepidoptera) and polyphagous beetles, such as Gonioctena quinquepunctata F. and Phyllobius sp. (Coleoptera), which prefer Prunus padus L. and P. serotina leaves [50][51][52][53]. Wounds are the gateway to infection by pathogens of this type [54].…”
Section: Discussionmentioning
confidence: 99%
“…Research in Poland (Karolewski et al, 2020) concluded that C. avellana and Prunus serotina Ehrh. (Black Cherry) received greater leaf damage than other understorey plants, and hosted a greater diversity and number of arthropod species.…”
Section: Herbivory and Diseasementioning
confidence: 99%